Pengaruh Sistem Pembayaran Digital dan Penerapan Sistem Informasi Akuntansi (SIA) Penjualan Terhadap Efektivitas dan Efisiensi Penjualan pada PT Sumber Alfariya Trijaya Tbk - Oktaria, Eka Travilta; Hermansyah, Hermansyah; Nugroho, Yudhinanto Cahyo; Hairudin, Hairudin (Lembaga Penelitian, dan Pengabdian Kepada Masyarakat (LPPM) STIE GENTIARAS Bandar Lampung dan berkolaborasi dengan Ikatan Akuntan Indonesia Kompartemen Akuntan Pendidik (IAI KAPd), 2024)
In a retail business, the use of technology can help business owners increasing their income, with increasingly tight competition where everything is required to be faster, more effective and efficient, both in terms of payment systems and sales transactions. The use of cash and recording sales is considered ineffective and inefficient because it takes a long time for each transaction and it is very easy for fraud, so the need for a digital payment system and sales accounting information system is needed so that the sales process system is well organized and automatic, moreover does not affect other aspects. The type of this research is quantitative research using primary data and egression test.